Nonlinear correlation between fatty liver index and carotid intima media thickness among individuals undergoing health examination - Zhou, Yuanchen; Duan, Shaojie; Wang, Rongrui; Chen, Jialiang; Yao, Shukun (Frontiers in Endocrinology, 2023)
Background Fatty liver index (FLI) is a predictor of non-alcohol fatty liver disease (NAFLD). This study aimed to assess the association between FLI and carotid intima media thickness (CIMT). Methods In this cross-sectional study, we enrolled 277 individuals for health examination from the China-Japan Friendship Hospital. Blood sampling and ultrasound examinations were conducted. Multivariate logistic regression and restricted cubic spline analyses were performed to evaluate the association between FLI and CIMT. Results Overall, 175 (63.2%) and 105 (37.9%) individuals had NAFLD and CIMT, respectively. The multivariate logistic regression analyses results showed that high FLI was independently associated with a high risk of increased CIMT, Q2 vs. Q1 (odds ratio [OR], 95% confidence interval [CI]): 2.35, 1.07–5.16, p = 0.033; Q3 vs. Q1 (OR, 95% CI): 1.7, 0.72–4.00, p = 0.222. The association between FLI and increased CIMT exhibited a J-shaped curve (nonlinear, p = 0.019). In the threshold analysis, the OR for developing increased CIMT was 1.031 (95% CI: 1.011–1.051, p = 0.0023) in participants with FLI < 64.247. Conclusion The relationship between FLI and increased CIMT in the health examination population is J-shaped, with an inflection point of 64.247.